1995
DOI: 10.1097/00005373-199506000-00016
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Absorbable Staple Fixation of Skin Grafts for Burn Wound Coverage

Abstract: A prospective randomized trial of absorbable versus metal skin staples for securing skin grafts to excised burn wounds was performed in 20 patients. The absorbable staples were easy to use and efficacious in securing the skin grafts, except to edematous fatty tissue. Aesthetically, the absorbable staples yielded as good or better results when compared with metal staples resulting from a lack of tissue distortion. A decrease of 61.4 minutes of the most significantly painful portion of the postoperative dressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In addition, staple fixation of skin grafts is associated with postoperative costs because of the time and labor required for their removal. 10 These factors should not be overlooked when conducting a benefit/risk evaluation of available treatments for standard of care. This study also included a number of patient-and investigator-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, staple fixation of skin grafts is associated with postoperative costs because of the time and labor required for their removal. 10 These factors should not be overlooked when conducting a benefit/risk evaluation of available treatments for standard of care. This study also included a number of patient-and investigator-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Staple removal can cause pain and anxiety in the patient and frequently requires intravenous analgesia and/or sedation, and in some instances conscious sedation or general anesthesia. 10,11 Staples can be difficult to remove in certain situations, such as areas of granulation tissue, 12,13 and retained staples have been reported to cause severe complications for the patient, if left in situ for extended periods of time. 14 -16 A previous randomized controlled study compared a fibrin sealant with an extended clotting time (fibrin sealant with 4 IU/ml thrombin) to staples in autologous split-thickness skin grafting in 40 burn patients.…”
mentioning
confidence: 99%
“…Because fibrin sealant biodegrades within 2 weeks, foreign bodies, such as sutures and staples, are not left in the wound, especially in the granulation bed. In addition, patients often report severe pain when staples are removed, and occasionally, an anesthetic procedure is required (O’Grady et al 2000; Batra et al 2016; Himel et al 1994; Best et al 1995; Ghosh et al 2015). Because fibrin sealant adheres to the entire surface, hematoma/seroma formation is significantly reduced compared with point-fixation sutures or staples (Cha et al 2012; Gibran et al 2007; Llanos et al 2006; Myer et al 2015; Mabrouk et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, MS share many of the disadvantages with traditional percutaneous sutures including the potential for staple track inflammation, bacterial migration into the wound bed, discomfort due to the presence of the staples and the requirements and costs associated with staple removal, which has been associated with considerable pain in man (Best et al . ).…”
Section: Introductionmentioning
confidence: 97%